Colonial Remains in Indonesian Fashion Blogipelago - Galant Nanta Adhitya; Novi Wulandari (Journal of Language and Literature, 2020)
This article aims to expose the colonial remains in Indonesian fashion blogipelago. It analyzes five Indonesian fashion bloggers: Anaz Siantar’s Brown Platform, Claradevi Handriatmaja’s Luce Dale, as well as Olivia Lazuardy’s, Ayla Dimitri’s and Sonia Eryka’s eponymous blogs. Since fashion blog exists in the interconnected cyberspace, this article is conducted under the scope of Transnational American Studies, approached with postcolonial theory. It then uses descriptive qualitative method in interpreting data gained from the aforementioned data, as well as the secondary ones. The finding comprises that the colonial remains are thus vividly apparent through the use of fashion blog formula by writing in English, wearing seasonal fashion, and shooting street photography abroad. This set of formulae helps Indonesian fashion bloggers to win the audience over. Therefore, the colonial remains in Indonesian fashion blogipelago are equally internalized both by the bloggers and the audience.